Exam MD-101 managing modern desktops (Microsoft Press, 2022)
7+ Hours of Video Instruction Includes coverage of the November 2021 exam updates! More than 7 hours of video instruction to help you manage your organization's Windows desktops and prepare for Exam MD-101 Managing Modern Desktops; one of the exams required to achieve Microsoft 365 Certified: Modern Desktop Administrator Associate. This engaging, self-paced instructional video course demonstrates how to deploy and upgrade operating systems, manage policies and profiles, manage and protect devices, and manage apps and data. If you're planning to take Exam MD-101 Managing Modern Desktops, this video course covers the exam objective domains published by Microsoft in a logical way for learning the technology and preparing for the exam. Throughout each lesson, Microsoft certified trainer and technical author Andrew Warren describes key concepts and puts them into action with demonstrations and real-world scenarios. About the Instructor Andrew Warren has more than 30 years of experience in the IT industry, many of which he has spent teaching and writing. He is a Microsoft Certified Trainer and has been involved as a subject matter expert in many of the Windows Server 2016 courses and as the technical lead in many Windows 10 courses. He also has been involved in developing TechNet sessions about Microsoft Exchange Server. He is the co-author of Exam Ref MD-100 Windows 10, Exam Ref MD-101 Managing Modern Desktops, Exam Ref 70-741 Networking with Windows Server 2016, and Exam Ref 70-742 Identity with Windows Server 2016 published by Microsoft Press. Andrew is based in the United Kingdom and lives in rural Somerset where he runs his own IT training and education consultancy. Learn How To Deploy and upgrade operating systems Manage policies and profiles Manage and protect devices Manage apps and data Who Should Take This Course IT professionals who deploy, configure, secure, manage, and monitor devices and client applications in an enterprise environment IT professionals who manage identity, access, policies, updates, and apps IT professionals who want to explore new and updated features in Windows Candidates preparing for Exam MD-101 Managing Modern Desktops Course Requirements Experience deploying, configuring, and maintaining Windows 10 and non-Windows devices Familiarity with M365 workloads.